Influence of Calcination Temperatures on Gunningite-Based Gelatin Template and Its Application as Ibuprofen Adsorption - Maria Ulfa; Muhammad Ari Purnama Ali (Indonesian Journal of Chemistry, 2022)
Gunningite has been successfully synthesized using the soft template method with the Pluronic F127-gelatin template. Gunningite was calcined at diverse temperatures of 500, 600, and 700 °C for 12 h and characterized by XRD, SEM, and FTIR. A UV-Vis Spectrophotometer measured the adsorption capacity of Gunningite against ibuprofen. The XRD results showed that the crystal sizes of Gunningite decreased from 35.41 to 28.31 nm with the increasing calcination temperature from 500 to 700 °C. Besides, the crystallinity degrees also increased from 49.94% to 56.13% as calcination temperature increased from 500 to 700 °C. The Gunningite formed aggregates in the form of tiny particles that merge and experience agglomeration. The FTIR spectra of the Gunningite samples demonstrated the functional groups –OH, Zn-OH, Zn-O-Zn, and gunningite vibrations. The maximum adsorption capacities of Gunningite to adsorb ibuprofen were 233.161 mg g−1 (500 °C), 219.543 mg g−1 (600 °C), and 227.033 mg g-1 (700 °C). The kinetic model of Gunningite on the ibuprofen adsorption followed the kinetic model of Ho and McKay.